Cerebrovascular complications in tuberculous meningitis—A magnetic resonance imaging study in 90 patients from a tertiary care hospital. Issue 1 (February 2020) - Soni, Neetu; Kumar, Sunil; Shimle, Anil; Ora, Manish; Bathla, Girish; Mishra, Prabhakar
Background: Cerebrovascular complications of tuberculous meningitis (TBM) are associated with increased morbidity and mortality. We retrospectively reviewed clinicoradiological findings of 90 TBM patients who presented to a tertiary care hospital, with emphasis on frequency and distribution of infarcts on diffusion imaging and pattern of vascular involvement on magnetic resonance (MR) angiography (MRA). Materials and methods: MR images of 90 TBM patients at presentation (2012–2018) were coanalyzed by two radiologists for tuberculomas, leptomeningeal enhancement (LM), hydrocephalus, infarct and vascular abnormalities. Infarcts were categorized based on location ("tubercular" (TB) or "ischemic" zones) and arterial supply (perforators and cortical branches). Clinical and laboratory findings were correlated with imaging data. Results: Ninety TBM patients (age 10–82 years) were enlisted after application of inclusion criteria. Tuberculomas were most common (100%) followed by LM (84.4%), cerebral infarcts (57.7%) and hydrocephalus (29%). Location-wise, 35% infarcts were in ischemic, 13% in TB and 15% in both zones. According to arterial supply, infarcts equally (50%) involved perforators from the lateral lenticulostriate and posterior cerebral (PCA)/basilar artery (BA) followed by medial lenticulostriate arteries (23%). MRA was available in 74.4% and abnormal in 43.2%. The middle cerebral artery was frequently involved (76%) followed by the anterior cerebral artery (38%), internal carotid artery (31%), PCA and BA. Six had diffuse narrowing with a paucity of distal vessels. Cerebral infarction was associated with hydrocephalus ( p = .0019) and vasculitis ( p < .001). Conclusion: In TBM, strokes are common and mainly involve the perforators and cortical branches. MR is the imaging modality of choice for early diagnosis and timely management.